The development of S-glycosylcysteine derivatives for use in glycan-binding assays - Williams, Matthew (Department of Chemistry, 2017)
This dissertation concerns the development of a synthetic route towards novel cysteine-based glycan-binding probes, for incorporation into glycoarrays and or similar applications used in assays of glycan-recognition phenomena. The need to systematically characterize the glycome and decipher the range of glycosylation patterns found in living cells, has prompted the development of molecular tools such as glycoarrays and related systems for immobilizing defined carbohydrate structures. The preparation of these probes requires access to building blocks where the core structure has defined glycans together with appropriate linkers, and the amino acid cysteine is explored here as one such structure. In particular, this dissertation describes the synthesis of a S-glucosylcysteine derivative SGC, or methyl N-(6-aminohexanoyl)-S-(β-D-glucopyranosyl)-L-cysteinate trifluoroacetate 67, as well as its 2-acetamido analogue SAGC, or methyl N-(6-aminohexanoyl)-S-(2-acetamido-2-deoxy-β-D-glucopyranosyl)-L-cysteinate trifluoroacetate 74. The first approach involved initial preparation of N-(4-azidobutanoyl)-L-cysteine 12 and attempted reaction of this with 1,2,3,4,6-penta-O-acetyl-β-D-glucopyranose 3 to form the initial target of this dissertation, bis-glucoside 13. This was not successful, but repetition of the reported reaction involving the use of N-acetyl-L-cysteine 4 provided a modest yield of partially purified bis-glucosyl cysteine (BGC, 1). A mechanism for this one-pot, sequential bis-glucosylation is proposed. The limitations of the one-pot procedure led to investigation of alternative methods for the step-wise introduction of sugar units to the cysteine core. For this purpose the cysteine derivative, methyl N-(6-((tert-butoxycarbonyl)amino)hexanoyl)-L-cysteinate 40, was prepared and reacted with 3 to obtain a fully protected precursor of the target SGC. However, inefficiencies in this procedure led to investigation of an alternative strategy for preparation of SGC.